Silica-Based Bioactive Glasses and Their Applications in Hard Tissue Regeneration: A Review - Nuha Al-Harbi; Hiba Mohammed; Yas Al-Hadeethi; Ahmed Samir Bakry; Ahmad Umar; Mahmoud Ali Hussein; Mona Aly Abbassy; Karthik Gurunath Vaidya; Ghada Al Berakdar; Elmoiz Merghni Mkawi; Manasa Nune (MDPI AG, 2021)
Regenerative medicine is a field that aims to influence and improvise the processes of tissue repair and restoration and to assist the body to heal and recover. In the field of hard tissue regeneration, bio-inert materials are being predominantly used, and there is a necessity to use bioactive materials that can help in better tissue-implant interactions and facilitate the healing and regeneration process. One such bioactive material that is being focused upon and studied extensively in the past few decades is bioactive glass (BG). The original bioactive glass (45S5) is composed of silicon dioxide, sodium dioxide, calcium oxide, and phosphorus pentoxide and is mainly referred to by its commercial name Bioglass. BG is mainly used for bone tissue regeneration due to its osteoconductivity and osteostimulation properties. The bioactivity of BG, however, is highly dependent on the compositional ratio of certain glass-forming system content. The manipulation of content ratio and the element compositional flexibility of BG-forming network developed other types of bioactive glasses with controllable chemical durability and chemical affinity with bone and bioactivity. This review article mainly discusses the basic information about silica-based bioactive glasses, including their composition, processing, and properties, as well as their medical applications such as in bone regeneration, as bone grafts, and as dental implant coatings.